O amor como fundamento ético-político n’A Cidade de Deus, de Santo Agostinho - Azevedo Segundo, Francisco Damazio de (2017)
The present dissertation objectifies depict the love as an ethical-political foundation in thinking of Aurelio Augustín, considering as foundation the book The City of God. The theme is necessary in front of ethical-political problems experienced in the contemporary, as the use of the State and the social institutions to the maintenance of social, racial, religious inequalities which unleashes in exclusion and suffering of neighbour. The hypothesis supported here is in respect to the love, while foundation and motivating of human‟s actions, therefore, it will be ascertained Augustinian ethical of love “where everything is Justice”, in order to be perceived the failure of ethical-political action when the citizens do not love what have to be loved. For this purpose, in order to this study be salutary, in the first moment it will be analyzed the place of ethics takes up in the mind of African philosopher. Subsequently, the analysis of the ethics and, finally, the study of love as an ethical-political foundation. The love presents itself as the foundation, however the focus in this study is in what must to be loved, in front of the problems experienced about social injustices discriminatory ideologies. The chapters are divided in three moments: the division philosophy perpetrated for the Bishop of Hippona in the aforesaid book, resulting platonic philosophy, in this case: the rational area, natural and moral; which, in turn, are ramifications of Socratic‟s thought, the contemplative knowledge and about the active knowledge. After arriving in the comprehension in what be the space of ethics, while the emerging point of view about the moral and, therefore, the active life, in what has aimed “love where everything Is Justice”, so it will be studied what is ethics. Therefore, the second part presents the concept of the Augustinian ethics, their categories, in order to be noted in what conditions a certain action can be understood as ethical or not. Therefore, it will be developed a research about the problem of existence of evil, in Manichean vision, that will be rejected for the African philosopher, which the scenary is the freewilland, consequently, the category of will, as well as the importance of love as “balance”, which tendency the man and, consequently, their actions. In the third chapter, the study will be focused in the analysis about the man‟s sociability which occurs by natural factors and contingents, in front of the freewill. Finally, it will be analysed the problem of relations between temporal time limit and everlasting law, in order to verify the conflicts between City Of Men and City Of God, in which is founded in love and, in its human itinerary, returns for the self-love, in order to find the happiness (beate vivere).